Origin of Kerr effect: investigation of solutions by polarization dependent Z-scan - Bundulis, Arturs; Mihailovs, Igors; Rutkis, Martins (Optical Society of America, 2020)
The nonlinear refractive index dependence on the incident light polarization state has been studied for pure chloroform and chloroform solutions of aminobenziliden-1,3-indandione derivatives. Measurements were done with linearly, elliptically, and circularly polarized light using 8 ns and 30 ps pulse duration 1064 nm lasers. This allows us to separate the electronic response, molecular reorientation, and thermo-optical components of the nonlinear refractive index. The refractive index variations with the change of laser pulse repetition rate were employed to identify the presence of the thermo-optical effect. Quantum chemical calculations of linear polarizability were used to estimate the magnitude of molecular-reorientation-induced refractive index changes for solvents and solutions. Overall, in this paper we have outlined various essential aspects that need to be taken into account to correctly interpret Z-scan measurement results for organic solvents and solutions.
This material is based upon work supported by the ERDF 1.1.1.1 activity project No. 1.1.1.1/16/A/046 “Application assessment of novel organic materials by prototyping of photonic devices”.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics